FINTECH AND SECURED TRANSACTIONS SYSTEMS OF THE FUTURE. - MOONEY JR., CHARLES W. (Law & Contemporary Problems, 2018)
The article offers information about fintech that include a claim that so called distributed ledger technology (DLT), blockchain technology is poised to revolutionize the financial markets. Topics discussed include ways in which fintech in secured transactions in the current legal and market environment as it primarily involves public and private registries; role of technology in the operations of registries; and possibilities for the future development of public and private registries.